Restitusi Sebagai Perwujudan Restorative Justice di Peradilan Indonesia - Putra, Rexy Meidi; Martha, Tawang Amuhara (PSHPM Untag Semarang, 2025)
Restorative justice has become a serious concern in the criminal justice system of Indonesia, as reflected in various regulations, such as the Juvenile Criminal Justice System Law and the National Criminal Code. One important aspect of this approach is restitution, which aims to restore the condition of victims due to criminal acts. Although regulations have accommodated restitution as part of restorative justice, its implementation still faces various obstacles. This article aims to analyze the effectiveness of fulfilling restitution in the Indonesian criminal justice system. The results of the research show that a gap still found between the judge's decision regarding restitution and the level of perpetrator compliance in paying it. Its Factors is weak law enforcement, lack of socialization, and minimal public legal awareness are the main problem in the enforcement of restitution. Therefore, efforts are needed to strengthen regulations, increase the role of law enforcement officers, and educate the public to ensure the effectiveness of restitution as a real manifestation of restorative justice in Indonesia.